Interleukin-18 genetics and inflammatory disease susceptibility - Thompson, S R; Humphries, S E (Genes and immunity, 2007)
IL18 was mapped to 11q22.2–22.3 in 1998. Owing to interleukin (IL)-18's important and novel role in immunomodulation, the gene itself has been subject to scrutiny, with the aim of discovering variants that may impact on disease susceptibility and/or progression. Despite being sequenced numerous times in different populations, no non-synonymous variants have been found. However, a number of polymorphisms within the proximal promoter have been verified that may interfere with transcription-factor-binding sites. Much of the subsequent association analyses have centred on these variants, but have yielded no consistent results, despite numerous different study populations being genotyped. IL18 has recently been resequenced in its entirety, enabling the tagging-single-nucleotide polymorphism (tSNP) methodology to be adopted. This approach has yielded interesting results, with genetic variation being shown to affect protein levels, and risk. This review aims to compile and reflect on the association data of interest published to date, with a focus on the diseases related to aberrant inflammatory control.